2011
DOI: 10.4161/nucl.2.3.15731
|View full text |Cite
|
Sign up to set email alerts
|

Post-natal myogenic and adipogenic developmental

Abstract: A-type lamins are a major component of the nuclear lamina. Mutations in the LMNA gene, which encodes the A-type lamins A and C, cause a set of phenotypically diverse diseases collectively called laminopathies. While adult LMNA null mice show various symptoms typically associated with laminopathies, the effect of loss of lamin A/C on early postnatal development is poorly understood. Here we developed a novel LMNA null mouse (LMNA GT-/-) based on genetrap technology and analyzed its early post-natal development.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

7
69
0

Year Published

2013
2013
2021
2021

Publication Types

Select...
5
2
2

Relationship

0
9

Authors

Journals

citations
Cited by 91 publications
(76 citation statements)
references
References 34 publications
7
69
0
Order By: Relevance
“…5K). Ectopic bone with MSC grafts has been found to be inhibited by RA and a RARG-specific agonist (57, 58), and RARG knockout mice also exhibit osteochondral defects and live only weeks longer than the few weeks that LMNA- deficient mice survive (5961). Chromatin-IP has thus far identified the RUNX2 gene to be a target of RA transcription factors but not yet SRF (fig.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…5K). Ectopic bone with MSC grafts has been found to be inhibited by RA and a RARG-specific agonist (57, 58), and RARG knockout mice also exhibit osteochondral defects and live only weeks longer than the few weeks that LMNA- deficient mice survive (5961). Chromatin-IP has thus far identified the RUNX2 gene to be a target of RA transcription factors but not yet SRF (fig.…”
Section: Resultsmentioning
confidence: 99%
“…LMNA knockout mice develop all tissues but die weeks after birth with growth retardation of connective tissues and also muscular dystrophy (5961) that is very severe compared with the prototypical mouse model of muscular dystrophy ( Dmd mdx ), which lives for 2 years (76). LMNA expression is therefore essential for maturation and survival against the incessant stressing in adult tissues, and once the lamin level matches to the stress, then the optimal level can enhance a prespecified lineage.…”
Section: Discussionmentioning
confidence: 99%
“…One report has suggested that these mice may not be complete knockouts but rather express a truncated prelamin A ( Jahn et al, 2012). Nonetheless, these mice and embryonic fibroblasts derived from them have been widely used to obtain important insights regarding the functions of lamin A and lamin C. Another gene trap Lmna knockout line has a shorter lifespan and does not develop left ventricular dilatation prior to death (Kubben et al, 2011). …”
Section: Mouse Models Of Cardiomyopathy Caused By Lmna Mutationsmentioning
confidence: 99%
“…Interestingly, an independent study showed that Lmna +/− mice develop severe cardiac abnormalities at 12 months of age analogous to those in humans with LMNA -mediated DCM (Wolf et al, 2008). Kubben et al created the Lmna GT/GT mouse model to study loss of function of Lmna (Kubben et al, 2011). Lmna GT/GT mice were created by placing a gene trap cassette between exon 1C and exon 2 of Lmna , which introduced the Lmna exon 1- or exon 1C-β -geo fusion allele.…”
Section: Variations In Nuclear Envelope Proteins Leading To Dcmmentioning
confidence: 99%